Levofloxacin Sequential Therapy vs Levofloxacin Triple Therapy in the Second‐Line Treatment of Helicobacter pylori: A Randomized Trial. (March 2016) - Liou, Jyh‐Ming; Bair, Ming‐Jong; Chen, Chieh‐Chang; Lee, Yi‐Chia; Chen, Mei‐Jyh; Chen, Chien‐Chuan; Tseng, Cheng‐Hao; Fang, Yu‐Jen; Lee, Ji‐Yuh; Yang, Tsung‐Hua; Luo, Jiing‐Chyuan; Wu, Jeng‐Yih; et al.
Abstract : Objectives: The efficacy of levofloxacin triple therapy has fallen below 80% in the second‐line treatment of Helicobacter pylori (H. pylori). We aimed to assess whether the levofloxacin sequential therapy is more effective than levofloxacin triple therapy in the second‐line treatment. Methods: This open‐label, randomized, multicenter trial was conducted between 2012 and 2015. H. pylori ‐infected subjects who failed from clarithromycin‐based regimens ( N =600) were randomized (1:1) to receive levofloxacin sequential therapy (LS: lansoprazole and amoxicillin for the first 5 days, followed by lansoprazole, levofloxacin, and metronidazole for another 5 days) or levofloxacin triple therapy (LT: lansoprazole, amoxicillin, and levofloxacin for 10 days). Successful eradication was defined as negative 13 C‐urea breath test at least 6 weeks after treatment. Our primary outcome was the eradication rate by intention‐to‐treat (ITT) and per‐protocol (PP) analyses. Antibiotic resistance was determined by agar dilution test. Results: The prevalence of clarithromycin, levofloxacin, and metronidazole resistance was 60, 17.6, and 36.9%, respectively. The eradication rates of LS and LT were 84.3% (253/300) and 75.3% (226/300), respectively, in the ITT analysis ( P =0.006) and 86.3% (253/293) and 78.8% (223/283), respectively, in the PP analysis ( P =0.021). The efficacies of both LS and LT were affected by levofloxacin resistance. The secondary resistance of levofloxacin was 66.7 and 73.9% after LS and LT, respectively. The efficacies of LS and LT were not affected by the CYP2C19 polymorphism. Conclusions: Levofloxacin sequential therapy was more effective than levofloxacin triple therapy, and it is recommended in the second‐line treatment for H. pylori (Trial registration number: NCT01537055).